After-School Programs: A Resource for Young Black Males and Other Urban Youth. (September 2016) - Woodland, Malcolm H.
While after-school programs are plentiful, they are often developed arbitrarily with little attention given to theoretical underpinnings that may inform program interventions. In this article, after-school programs are situated in resilience theory as protective factors, which encourage resilience among young Black males and other urban youth. The resilience literature is explored, granting attention to varying resilience models and contextualizing resilience in young Black males. Several risk factors such as poverty, violence exposure, and academic difficulty, which often plague these young men, are also examined. Finally, after-school programs are introduced as resources for Black males and other urban youth.